Statistics, Data Mining, and Machine Learning in Astronomy : A Practical Python Guide for the Analysis of Survey Data - Ivezić, Željko; Gray, Alexander (Alexander G.); Vanderplas, Jacob T.; Connolly, Andrew (Andrew J.) (Book collections on Project MUSE., 2014)
More specifically, "this book is mostly about how to estimate the empirical pdf [probability density function] f(x) from data (including multidimensional cases), how to statistically describe the resulting estimate and its uncertainty, how to compare it to models specified via h(x) (including estimates of model parameters that describe h(x)), and how to use this knowledge to interpret additional and/or new measurements (including best-fit model reassessment and classification)."--Print version, Page 8